ANALISIS KETERPADUAN PEMBELAJARAN DALAM PEMBUATAN MODUL AJAR IPAS KELAS V SEKOLAH DASAR - Alfiyah Maulani; Anggit Merliana (Jurnal Binagogik, 2024)
The independent curriculum is an alternative curriculum used post-endemic in the face of learning setbacks which provides freedom with the term "Freedom to Learn" in the implementation of learning that involves the entire school community. The independent curriculum was created to develop the needs and potential of students. Regarding integrated learning, this independent curriculum is not like the 2013 curriculum which links several concepts to scientific disciplines or what is usually called thematic. This independent curriculum is also reminiscent of the 2006 Education Unit Level Curriculum (KTSP), where learning disciplines are separate. This research aims to provide an overview of the preparation of good and correct learning planning. Learning planning in the independent curriculum is known as teaching modules. The research uses the Library Research (Library Study) method and teaching module documents to support analysis. There are components that need to be considered when creating a teaching module. Based on the analysis, there is no written integration in the implementation of science and science learning in elementary schools. Apart from that, the completeness of the learning support in the teaching module is incomplete. There are several other analyzes regarding the suitability of the Teaching Module Components in measuring the level of student success. However, the teaching module can be said to be appropriate if used with fifth grade elementary school students because it is appropriate to learning outcomes. The advantages and disadvantages contained in the teaching module can be evaluated by the teacher, so that learning objectives can be achieved optimally.